Imidazole propionate is increased in diabetes and associated with dietary patterns and altered microbial ecology - Molinaro, Antonio; Bel Lassen, Pierre; Henricsson, Marcus; Wu, Hao; Adriouch, Solia; Belda, Eugeni; Chakaroun, Rima; Nielsen, Trine; Bergh, Per-Olof; Rouault, Christine; André, Sébastien; Marquet, Florian; et al. (Nature Communications, 2020)
Microbiota-host-diet interactions contribute to the development of metabolic diseases. Imidazole propionate is a novel microbially produced metabolite from histidine, which impairs glucose metabolism. Here, we show that subjects with prediabetes and diabetes in the MetaCardis cohort from three European countries have elevated serum imidazole propionate levels. Furthermore, imidazole propionate levels were increased in subjects with low bacterial gene richness and Bacteroides 2 enterotype, which have previously been associated with obesity. The Bacteroides 2 enterotype was also associated with increased abundance of the genes involved in imidazole propionate biosynthesis from dietary histidine. Since patients and controls did not differ in their histidine dietary intake, the elevated levels of imidazole propionate in type 2 diabetes likely reflects altered microbial metabolism of histidine, rather than histidine intake per se. Thus the microbiota may contribute to type 2 diabetes by generating imidazole propionate that can modulate host inflammation and metabolism.